Tran Thien Cuong Study on Soil and Water Environment in Coal Mining Area at Lo Tri Coal Mine, Quang Ninh Province - Trần Thiện, Cường (VNU Journal of Science: Earth and Environmental Sciences, 2017)
Lo Tri coal mine is located on Nhen Mountain, Cam Dong Ward, Cam Pha City, Quang Ninh Province, which is managed and operated by Thong Nhat Coal Company. The results showed that the effluents from the mine are characterized by low pH (3.17), high contents of TSS, Fe and Mn (TSS: 566.4 mg/l; Fe: 26.55 mg/l; Mn: 3.34 mg/l). After being treated through the treatment system, the pH of the water became alkaline, Fe and Mn contents were below the standard thresholds, while the TSS was still 1.5 times higher than that of the QCVN 40:2011 /BTNMT. The results also showed that the water quality in Ngo Quyen stream (receiving waste water from the mine) was contaminated (TSS values in both samples were higher than that of the QCVN 08-MT: 2015/BTNMT by 1.28 to 1.31 times; 1/2 samples of Fe and Mn sample values were 1.56 times and 1.2 times higher than QCVN limits, respectively). For soil samples, all three samples analyzed showed that Pb, Cu and Zn contents were higher than limits set by the QCVN 03-MT: 2015/BTNMT for industrial land (Pb was 2.5 times, Cu: 1.9 times and Zn 2.6 times higher than standards). This demonstrates that the management and monitoring of pollution at site is not practically effective which presents substantial threats to the surrounding environment.